2015
DOI: 10.1617/s11527-015-0527-4
|View full text |Cite
|
Sign up to set email alerts
|

TC 238-SCM: hydration and microstructure of concrete with SCMs

Abstract: This paper is the work of working group 2 of the RILEM TC 238-SCM. Its purpose is to review methods to estimate the degree of reaction of supplementary cementitious materials in blended (or composite) cement pastes. We do not consider explicitly the wider issues of the influence of SCMs on hydration kinetics, nor the measurement of degree of reaction in alkali activated materials. The paper categorises the techniques into direct methods and indirect methods. Direct methods attempt to measure directly the amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
108
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(131 citation statements)
references
References 57 publications
3
108
0
1
Order By: Relevance
“…The reproducible contrast of BSE images makes them well suited to use in achieving this aim. Scrivener et al (1986) have shown that the amount of unreacted cement measured by BSE and image analysis corresponds well with independent measures of hydration, and this has also been demonstrated to be highly effective for determination of the extent of reaction of supplementary cementitious materials in blends containing PC (Wong et al, 2006;Scrivener et al, 2015). However, the situation is likely to be different for the study of porosity, which is usually present in discrete regions that are much smaller than the anhydrous cement (or slag) particles.…”
mentioning
confidence: 84%
“…The reproducible contrast of BSE images makes them well suited to use in achieving this aim. Scrivener et al (1986) have shown that the amount of unreacted cement measured by BSE and image analysis corresponds well with independent measures of hydration, and this has also been demonstrated to be highly effective for determination of the extent of reaction of supplementary cementitious materials in blends containing PC (Wong et al, 2006;Scrivener et al, 2015). However, the situation is likely to be different for the study of porosity, which is usually present in discrete regions that are much smaller than the anhydrous cement (or slag) particles.…”
mentioning
confidence: 84%
“…High performance concrete (lower w/b ratio), for example, is very prone to early age cracking induced by self-desiccation and autogenous deformation [13,15]. High content of GGBS also leads to increased chemical shrinkage due to its filler effect and greater hydration degree [1,4,5]. Thus, SAPs showed themselves as a great shrinkage reducer in GGBS-PC matrices (Fig.…”
Section: Cmss-2017mentioning
confidence: 99%
“…Its ability to slow down cementitious reactions and induce a filler effect leads to a denser CH-laden interfacial zone and formation of finer capillaries, in particular, those in the mesopore range [1,2,6,36]. Fig.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of reaction of fly ash in fly ash cement blended system are determined using methods like the selective acid dissolution Glasser 1987, 1998;Sakai et al 2005;Ohsawa et al1985;Suprenant and Papadopoulos 1991;Li et al1985;Fernández-Jiménez et al 2006;Haha et al 2010;Scrivener et al 2015), NMR analysis (Brunet et al 2010), backscattered electron imaging (Deschner et al 2013;Feng et al 2004) SCM with energy dispersive spectroscopy (EDS) (Durdziński et al 2015a) and mass balance (Deschner et al 2012). Among all the methods, selective dissolution is the most widely used method to determine the reaction of fly ash.…”
Section: Introductionmentioning
confidence: 99%